Design optimization of an Archimedes screw turbine for hydrokinetic applications using the response surface methodology (2021)
In this study, the performance of an Archimedes screw turbine (AST), in terms of the power coefficient (CP), was evaluated. The design parameters, including the inner and the outer diameter (Di and Do, respectively), the axle length (L), the blade inclination with respect to the longitudinal axis of the screw (α) and the blade stride (p), were selected as the studied factors to be optimized by using the response surface methodology and particularly a central composite design of experiments (CCD) to maximize the CP value. Computational fluid dynamics simulations were conducted to investigate the interaction among the referred parameters on the turbine performance. In the numerical simulation, six degrees of freedom (6-DoF) user defined function (UDF) method was used. Furthermore, the results obtained for the initial and the optimized turbine configurations were compared based on the experimental data available in the literature. The numerical results showed a good agreement with the reported experimental data. The highest CP values obtained under optimal design conditions; i.e., at aDi/Do, L, α and a p equal to 0.1, 360 mm, 73.94∘ and 220 mm, respectively, were 0.5515 (CFD result) and 0.5137 (predicted value derived from the validated reduced second-order regression model).